Lower Functional and Proportional Characteristics of Cord Blood Treg of Male Newborns Compared with Female Newborns - Černý, Viktor; Novotná, Olga; Petrásková, Petra; Hudcová, Kateřina; Boráková, Kristýna; Prokešová, Ludmila; Kolářová, Libuše; Hrdý, Jiří (Biomedicines, 2021)
Understanding the early events involved in the induction of immune tolerance to harmless environmental antigens and microbiota compounds could reveal potential targets for allergic disease therapy or prevention. Regulatory T cells (Treg), particularly induced Treg (iTreg), are crucial for the induction and maintenance of tolerance against environmental antigens including allergens. A decrease in the number and/or function of Treg or iTreg could represent an early predictor of allergy development. We analyzed proportional and functional properties of Treg in the cord blood of children of allergic mothers (neonates at high risk of allergy development) and healthy mothers (neonates with relatively low risk of allergy development). We observed a higher number of induced Treg in the cord blood of females compared to males, suggesting an impaired capacity of male immunity to set up tolerance to allergens, which could contribute to the higher incidence of allergy observed in male infants. The decreased proportion of iTreg in cord blood compared with maternal peripheral blood documents the general immaturity of the neonatal immune system. We observed a positive correlation in the demethylation of the Treg-specific demethylated region (TSDR) and the proportion of Treg in cord blood. Our data suggest that immaturity of the neonatal immune system is more severe in males, predisposing them to increased risk of allergy development.
Keywords: flow cytometry; TSDR; natural Treg; Helios; regulatory T cells; cord blood; induced Treg; allergy; epigenetics